From Clinical Trials to Highly Trustable Clinical Trials: Blockchain in Clinical Trials, a Game Changer for Improving Transparency? - Benchoufi, Mehdi; Altman, Doug; Ravaud, Philippe (Frontiers in Blockchain, 2019)
The quality of clinical research is undermined by severe misconduct, error, and fraud, which are detrimental to the trust it should arouse. In this perspective article, we show how Blockchain may trace and control processes of clinical trials to prevent these issues or at least discourage them because they would become traceable and averted. Then, we propose a short and doable program in which, amid the complex stream of events in a clinical trial, we select sensitive and misconduct-prone steps that could greatly benefit from Blockchain by its simple core features such as traceability and incorruptibility of data registration or more refined automation tools called Smart Contracts.